2020
DOI: 10.1111/1541-4329.12177
|View full text |Cite
|
Sign up to set email alerts
|

Graduate capabilities required of South African food science and technology students

Abstract: South African societal stakeholders are in general not satisfied with the work preparedness of newly graduated food science and technology students. There is currently little local literature available that defines the graduate capabilities required of newly graduated food scientists and technologists in South Africa. Therefore, the outcomes of an empirical analysis conducted through stakeholder engagement to identify the required graduate capabilities of newly graduated students in food science and technology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The pressure to produce employable graduates is an issue in virtually all countries—both developing and developed (Grotkowska et al, 2015; Jenkins & Lane, 2019; Metcalfe et al, 2020; Mok et al, 2016; Small et al, 2018). This is largely manifested in the onus on universities to churn out well-trained and employable graduates.…”
Section: Graduate Employability: Global Overviewmentioning
confidence: 99%
“…The pressure to produce employable graduates is an issue in virtually all countries—both developing and developed (Grotkowska et al, 2015; Jenkins & Lane, 2019; Metcalfe et al, 2020; Mok et al, 2016; Small et al, 2018). This is largely manifested in the onus on universities to churn out well-trained and employable graduates.…”
Section: Graduate Employability: Global Overviewmentioning
confidence: 99%
“…Thus, the skills listed by our respondents largely overlap with these standards. Similarly, other studies that have examined what food science educators and industry professionals think are important outside the United States have also identified that communication, business skills, teamwork, and knowledge of disciplinary skills are essential competencies for food science (Flynn et al., 2013; Mayor et al., 2015; Metcalfe et al., 2020; Weston et al., 2017, 2020). Interestingly, past work has found major variation in the skills that food science industry professionals identify as important based on geographic region, suggesting that more work is needed to explore if our results—and the standards listed by IFT's HERB—are representative of what food science communities in other parts of the United States identify as the most critical skills for food science students and professionals to develop (Flynn et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, graduate employability is not a problem for the developed countries, it is a global problem [28,25,29,30,31]. But developing and least developed countries are still far behind compared to the developed world in both developing curricula and policy making for better graduate employability outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%